Can Upper Airway Surgeries Improve Lower Airway Function ? A Prospective Study - Arifa, K. A.; Nayana, V. G.; Irfan, K. M. (Indian journal of otolaryngology, and head, and neck surgery, 2022)
Deviated nasal septum and turbinate hypertrophy are the most common causes for nasal obstruction, which compromise nasal airflow and increases airway resistance. These conditions can further reduce the airflow to lung, which will affect the lung volume and function subsequently reduces the exercise tolerance. The present study aimed to evaluate the impact of upper airway surgeries like septoplasty and turbinoplasty on lower airway functions using simple tests like spirometry and 6 min walking test (6mWt). This research was a prospective study. There were 88 subjects in the study who completed follow up. Spirometry and 6mWt was performed 1 day before and 1 month after surgery in all subjects. Mean preoperative and postoperative values of spirometry (forced vital capacity (FVC),forced expiratory volume in 1 s (FEV1), forced expiratory volume in 1 s/ forced vital capacity (FEV1/FVC), peak expiratory flow rate (PEFR) and 6mWt (systolic blood pressure, diastolic blood pressure, heart rate and oxygen saturation) parameters were compared and analyzed. Percentage of improvement of each parameter was compared with the type of surgery, side of obstruction, age of the patient and duration of symptom. Spirometry showed statistically significant improvement in all 4 parameters after surgery in 86 subjects. 6mWt showed statistically significant improvement in SBP and SpO2 and there was no significant improvement in DBP and HR. We also observed that improvement in parameters was irrespective of age and duration of symptoms. So this study concludes that airway narrowing nasal diseases can compromise lower airway function.